If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -14 + 30c + -2y + 16c = 0 Reorder the terms: -14 + 30c + 16c + y + -2y = 0 Combine like terms: 30c + 16c = 46c -14 + 46c + y + -2y = 0 Combine like terms: y + -2y = -1y -14 + 46c + -1y = 0 Solving -14 + 46c + -1y = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 46c + 14 + -1y = 0 + 14 Reorder the terms: -14 + 14 + 46c + -1y = 0 + 14 Combine like terms: -14 + 14 = 0 0 + 46c + -1y = 0 + 14 46c + -1y = 0 + 14 Combine like terms: 0 + 14 = 14 46c + -1y = 14 Add 'y' to each side of the equation. 46c + -1y + y = 14 + y Combine like terms: -1y + y = 0 46c + 0 = 14 + y 46c = 14 + y Divide each side by '46'. c = 0.3043478261 + 0.02173913043y Simplifying c = 0.3043478261 + 0.02173913043y
| 19m=7 | | 0.50x+0.20(130)=0.25(140) | | 8y-6(3y-7)= | | 15x-5+3x=8x+5 | | 5(7+3x)-12= | | 19u=-7 | | -15.00+0.39x=50 | | (d+2)(d+6)-y(y+5)=24 | | 5x-6=35x+6 | | -4(5a-3b)= | | 3x+(-17)+21f+3x-(21f)= | | -2=2v-6 | | p^2-14p-15=0 | | 5x-6=35+6 | | 6y^2-y+7=0 | | 4x+3xy=6y | | -3y+1=-2(3y+13) | | A+12=5a-4+a | | X^2-4X-2m=0 | | 3x^3-33=0 | | 3x-1-5=20x | | -4y+2=3(2y+2) | | 7x+11=10+3x+9 | | 3t-1/8=t-4/16+t-2/16 | | 12r+5s-7t+11r+9s-4r= | | 16x^2+28x+10= | | y-5=0.33(x-4) | | 8x-9x-7=3-3x | | 4x+2-9x-3=0 | | 94=4x+14 | | 45+x=1282-2x | | y-1=0.5(x+3) |